Effect of Feed Restriction on Basal Steroid Hormone Levels, and Egg Production in the Layer - - (Agriculture and Natural Resources, 1992)
The effect of feed restriction on basal steroid hormone levels, and egg production in the layer was studied. Two feed restriction programs; in which the 12-week-old chickens had access to feed for 8h a day (8h-fed group), and had each day for 85% of the calculated amount of feed consumed by the conventional full fed (85%-fed group), were compared with a free-feeding program in which the chicken received the same diet but on an ad libitum basis (ad libitum group). The results showed that serum progesterone and estradiol levels of the three groups were generally increased with age from growing to laying period. The 8h-fed and 85%-fed groups were inclined to have lower levels of progesterone and estradiol than the ad libitum group. Testosterone content, on the other hand, showed no certain pattern of change with either the age or feeding program. Whereas the feed restriction did not affect the age, body weight, and egg weight at the onset of lay, it resulted in delay on age, a heavier body weight and a larger egg size at the 50% egg production. The effect on hen-day egg production was obvious. From the onset of lay to 40 weeks of age, the ad libitum, 8h-fed, and 85%-fed chickens laid 89.7, 61.0, and 49.9 eggs/bird, respectively (p<0.05). The depressing effect on egg production was lifted once the restricted birds were turned to the full feeding. The cumulative number of eggs produced during the period from 40-72w. of the 8h-fed turned full-fed, and 85%-fed turned full-fed groups were 143.9 and 155.2 eggs/bird, respectively compared with the 128.0 egg/bird of the ad libitum group (p<0.05). A similar depressing effect of feed restriction was also true on the feed conversion rate (kg. feed consumed/kg. egg produced).